Entrepreneurship Education: A Systematic Literature Review and Identification of an Existing Gap in the Field - Francisco Banha; Luís Serra Coelho; Adão Flores (MDPI AG, 2022)
Having identified the need to conduct research on the intersection between entrepreneurship education (EE) and public policies, we carried out a systematic literature review on decision-making processes regarding the implementation of education for entrepreneurship programs in schools and the introduction of this topic in the policy-making process. This SLR followed every process inherent to its well-established protocol. The research undertaken confirmed that the understanding of decision processes associated with the implementation of EE programs is not only a "missing link" in the discussions about the way in which countries manage situations related to EE, but also a gap in academic knowledge. Indeed, the SLR process included only nine articles in the final review (obtained through a methodology based on an algorithm)-which is a clear sign that further scientific research around this specific topic is needed. The articles included in the final review suggest that: (i) entrepreneurship is fundamental to the progress and evolution of countries and their regions, (ii) there is evidence that EE is central to a more entrepreneurial youth, and (iii) the successful implementation of recommendations from regulatory institutions is based on political commitment and implementation capacities.